2016
DOI: 10.3389/fmicb.2016.00237
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Timing and Dosage of a Fluoroquinolone Treatment on the Microbiological, Pathological, and Clinical Outcomes of Calves Challenged with Mannheimia haemolytica

Abstract: The efficacy of an early and low inoculum-adjusted marbofloxacin treatment was evaluated on microbiological and clinical outcomes in calves infected with 4.107 CFU of Mannheimia haemolytica A1. Twenty-two calves were included based on their rectal temperature rise in the 10 h after challenge and allocated in four groups, receiving a single intramuscular injection of saline (CON), 2 mg/kg marbofloxacin 2–4 h after inclusion (early treatment, E2), 2 or 10 mg/kg marbofloxacin 35–39 h after inclusion (late treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 49 publications
0
36
0
Order By: Relevance
“…New techniques of bovine respiratory diseases diagnostics, such as cough captors or ruminal temperature boluses, can be used to monitor early signs of illness before appearance of clinical signs (Timsit et al, 2011a,b). Recent studies conducted with mice and calves suggested that a decrease in the administered dose of fluoroquinolone allowed achievement of similar bacterial cure, when low bacterial inocula are targeted and the disease is detected early (Ferran et al, 2011; Lhermie et al, 2016). These protocols significantly decrease the amount of antibiotic required to reach a similar clinical efficacy.…”
Section: Priority Actions To Minimize the Impact Of Veterinary Antimimentioning
confidence: 99%
“…New techniques of bovine respiratory diseases diagnostics, such as cough captors or ruminal temperature boluses, can be used to monitor early signs of illness before appearance of clinical signs (Timsit et al, 2011a,b). Recent studies conducted with mice and calves suggested that a decrease in the administered dose of fluoroquinolone allowed achievement of similar bacterial cure, when low bacterial inocula are targeted and the disease is detected early (Ferran et al, 2011; Lhermie et al, 2016). These protocols significantly decrease the amount of antibiotic required to reach a similar clinical efficacy.…”
Section: Priority Actions To Minimize the Impact Of Veterinary Antimimentioning
confidence: 99%
“…In North America and many countries, macrolides are often given as BRD metaphylaxis to asymptomatic animals in the presence of diseased animals. Individual cattle symptomatic for BRD may also be treated with a wide range of antimicrobials, with the fluoroquinolone marbofloxacin used in this manner [97]. Clinical symptoms may only become apparent after pulmonary damage has occurred.…”
Section: Antimicrobial Resistance In Bovine Pathogensmentioning
confidence: 99%
“…In calves experimentally infected with M. haemolytica (4 × 10 7  CFU), Lhermie et al [97] demonstrated that low-dose (2 mg/kg) marbofloxacin 12 h after inoculation eliminated this pathogen from all calves, but at 45 h post-inoculation a high-dose (10 mg/kg) failed to do so. Since M. haemolytica persisted after this high-dose, a higher risk for AMR development may have been created by a practice thought to be more judicious than mass medication [97].…”
Section: Antimicrobial Resistance In Bovine Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Although conflicting evidence is available on whether human, companion, and/or livestock medicine is responsible for the emergence of antimicrobial resistance [13, 14], the livestock industry has been recognized as one of the main causes [13, 15], perhaps due to the amount of antimicrobials used in this sector [16], affecting humans either through direct contact or through the food chain [17, 18]. The increasing demand for animal protein is believed to be accompanied by a significant growth in need for antimicrobial use in food animal production, which is predicted to rise by approximately 67% between 2010 and 2030 [17]. Responsible use of antimicrobials in food animals is paramount for maintenance of both animal and human health [19] and has been one of the policies proposed by the One Health Initiative [2022].…”
Section: Introductionmentioning
confidence: 99%